Toxicity Evaluation of Anti‐cholinesterasic Amphibian Extracts by MTT and an Optimized Artemia salina Test - Spinelli, Roque (2023)
The amphibian skin is an important source of bioactive compounds. Recently, our workgroup reported the bioactivity of new extracts from the Hylidae, Microhylidae and Leptodactylidae families against several pathways involved in Alzheimer's disease. However, since cytotoxicity can be a limiting factor for their applicability, we evaluated the toxicity of nine amphibian skin extracts with reported anticholinesterase activity, using the traditional MTT assay and an optimized Artemia salina test. The proposed improvement, guided by experimental design, aims to reduce the amount of biological sample needed. Overall, we proved that the active extracts were non-toxic at effective concentration against cholinesterases (AChE/BChE), positioning the amphibian skin as a promising and preliminary safe source of bioactive compounds in the anti-Alzheimer's treatment. Interestingly, we demonstrated that both toxicity assays can discriminate between toxic and non-toxic samples. We propose the A. salina bioassay as a reliable and cost-effective alternative for early toxicity screening.